EFEKTIVITAS KOMUNIKASI INTERPERSONAL DALAM KEGIATAN PEMBELAJARAN MELALUI MEDIA WHATSAPP GROUP - Sepriadi Saputra (Professional: Jurnal Komunikasi dan Administrasi Publik, 2020)
This study aims to know the effectivity of interpersonal communication in learning activities through WhatsApp Group Media, a research study using an effectiveness study proposed by Devito (1997) which says there are 5 general dimensions to measure the effectiveness of interpersonal communication activities including openness, empathy, supportive, attitude positive and equality. Based on the results of the presentation about the effectiveness of interpersonal communication in lectures using WhatsApp Group by the Communication Studies lecturer at the Raden Fatah State Islamic University of Palembang, it is known that WhatsApp Group can display various types of learning media in the form of visual media, audio, audio visual, and presenter groups. However, the WhatsApp group media cannot provide sample objects directly if the course requires sample objects to be demonstrated. This research shows that learning activities that only use WhatsApp Group media without using face-to-face lecture methods are ineffective, this is due to the many obstacles faced by students and lecturers when the lecture activities take place. Various obstacles faced are the small level of openness of students, empathy that is difficult to show both by students and by lecturers, the attitude of support is not as strong as learning is done by direct meeting in class, the attitude shown is largely the opposite of what is expected by the lecturer, as well as the equality of the meaning of learning materials both for students and for different lecturers. Keywords: interpersonal communication, openness, empathy, supportiveness, positive attitude and equality, whatsapp group